Pembelajaran Matematika Di Desa Weekura Dengan PMRI dan Model Pembelajaran Dragon Ball - Making, Samuel Rex Mulyadi; Napu, Timotius Woda (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2024)
The problem in Wee Kura Village is that elementary school age children consider mathematics to be one of the most difficult subjects. Many elementary school age children are afraid of mathematics. One approach that can be used in learning mathematics is PMRI using the Dragon Ball Learning Model. The aim of this community service is to increase the understanding of elementary school age children through the PMRI approach using the Dragon Ball learning model. It is hoped that this community service activity will be able to overcome the problems of elementary school age children. Methods for carrying out activities include observation, preparation of service instruments, implementation of mathematics learning, evaluation and reporting. Learning activities are carried out outside school hours. The pretest results obtained the highest score of 75 and the lowest score of 45, while the average score was 60. For the posttest score, the highest score was 100 and the lowest score was 70, while the average score was 85. There was an increase in understanding abilities for elementary school age children. The interview results show that children are enthusiastic about learning mathematics, they can learn mathematics with fun approaches and method